Pain Induced Changes in Brain Oxyhemoglobin: A Systematic Review and Meta-Analysis of Functional NIRS Studies. Issue 6 (28th February 2021) - Hall, MacGregor; Kidgell, Dawson; Perraton, Luke; Morrissey, Jack; Jaberzadeh, Shapour
Abstract: Background: Neuroimaging studies show that nociceptive stimuli elicit responses in an extensive cortical network. Functional near-infrared spectroscopy (fNIRS) allows for functional assessment of changes in oxyhemoglobin (HbO), an indirect index for cortical activity. Unlike functional magnetic resonance imaging (fMRI), fNIRS is portable, relatively inexpensive, and allows subjects greater function. No systematic review or meta-analysis has drawn together the data from existing literature of fNIRS studies on the effects of experimental pain on oxyhemoglobin changes in the superficial areas of the brain. Objectives: To investigate the effects of experimental pain on brain fNIRS measures in the prefrontal-cortex and the sensory-motor-area; to determine whether there is a difference in oxyhemodynamics between the prefrontal-cortex and sensory-motor-area during pain processing; to determine if there are differences in HbO between patients with centralized persistent pain and healthy controls. Methods: Studies that used fNIRS to record changes in oxyhemodynamics in prefrontal-cortex or sensory-motor-cortex in noxious and innoxious conditions were included. In total, 13 studies were included in the meta-analysis. Results: Pain has a significantly greater effect on pre-frontal-cortex and sensory-motor areas than nonpainful stimulation on oxyhemodynamics. The effect of pain on sensory-motor areas was greater than the effect of pain on the prefrontal-cortex. There was an effect of centralized pain in the CPP group on oxyhemodynamics from a noxious stimulus compared to control's response to pain. Conclusions: Pain affects the prefrontal and sensory-motor cortices of the brain and can be measured using fNIRS. Implications of this study may lead to a simple and readily accessible objective measure of pain.